Angiography features of early onset drusen. Issue 2 (7th July 2010) - Guigui, Benjamin; Leveziel, Nicolas; Martinet, Virginie; Massamba, Nathalie; Sterkers, Margaret; Coscas, Gabriel; Souied, Eric H
Abstract : Aims: Drusen are rarely observed in patients <50 years of age. Two types of early onset drusen (EOD) are commonly described: basal laminar drusen (BLD) and drusen associated with Malattia Leventinese (ML). Our purpose was to classify the phenotype of EOD on the basis of fundus examination, and fluorescein angiography (FA) and indocyanine green angiography (ICGA) features. Methods: We performed a prospective study including 48 consecutive EOD patients. All of them had a complete ophthalmologic examination including FA and ICGA. Results: BLD (67%) were extremely hyperfluorescent on FA and ICGA. ML (10%) was characterised by a combination of small radial and large round drusen with differences in staining in both FA and ICGA. We evidenced a third type of EOD (23%) harbouring an aspect of large colloid drusen (LCD), mildly hyperfluorescent in the early phases of FA, with a progressive staining in late phases. In intermediate and late phases of ICGA, LCD presented as hypofluorescent dot surrounded by a hyperfluorescent halo bordered by a thin hypofluorescent ring. Conclusion: Three types of EOD are distinguished by their FA and ICGA features. We report a new kind of juvenile drusen, distinct from BLD and ML, named LCD, associated with a good vision and absence of complications.